Jujuboside B Inhibits the Proliferation and Migration of Non-Small Cell Lung Cancer H1299 Cells Through Inhibiting PI3K/Akt and Wnt/β-Catenin Pathways - Chen M; Li J; Hu S; Wang Y; Wang K; Wang T (Cancer Management and Research)
Mengzhu Chen,1 Jian Li,1 Shaodan Hu,1 Yuhan Wang,2 Keju Wang,1 Tan Wang1 1Department of Respiratory, The Affiliated Hospital to Changchun University of Chinese Medicine, Changchun, 130021, People’s Republic of China; 2School of Traditional Chinese Medicine, Changchun University of Chinese Medicine, Changchun, 130117, People’s Republic of ChinaCorrespondence: Tan Wang, Email wangtan0688@126.comBackground: Lung cancer has high incidence and mortality rates. In consideration of the high toxicity and side effects of traditional chemical drugs and drug resistance, researchers have substituted some natural products for anti-lung cancer drugs. Ziziphi spinosae semen (ZSS) is a famous traditional Chinese herb, and ZSS-based formulas have been used against lung cancer in clinic, such as Xiaoyi Sanjie Formula. Jujuboside B (JUB) is one of the main bioactive components in ZSS; however, JUB’s roles in the treatment of lung cancer, and the mechanism have not been well reported.Objective: This study intends to evaluate the effects of JUB on the proliferation and migration of non-small cell lung cancer H1299 cells (NC-1299 cells), as well as the potential related regulatory mechanism.Methods: The viability, migration and invasive ability of NC-1299 cells were analyzed by CCK8, wound-healing, transwell invasion, and the expression of proteins was analyzed through Western blotting experiments.Results: It showed that 160 and 320 μmol/L JUB significantly inhibited the proliferation of NC-1299 cells, reduced the cell migration in the wound healing test, and decreased the cell number of clonal assay (P < 0.05). JUB also significantly inhibited the expression of Vimentin, MMP2, and MMP9 proteins related to the migration and invasion of tumor cells, as well as inhibited the PI3K/AKT and Wnt/β-catenin pathways.Conclusion: The results indicate JUB has a significant inhibitory effect on NC-1299 cells, and such inhibitory effect is associated with inhibiting the expression of migration and invasive proteins such as MMP2, as well as inhibiting the PI3K/AKT and Wnt/β-catenin pathways. The findings provide some references for the application of JUB in the substitution of anti-lung cancer drugs. Keywords: Jujuboside B, non-small cell human lung cancer NC-1299 cells, proliferation, migration, PI3K/AKT, Wnt/β-catenin